Science and Engineering of Casting Solidification - Stefanescu, Doru Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The 3rd edition of this popular textbook covers current topics in all areas of casting solidification. Partial differential equations and numerical analysis are used extensively throughout the text, with numerous calculation examples, to help the reader in achieving a working knowledge of computational solidification modeling. The features of this new edition include: • new chapters on semi-solid  and metal matrix composites solidification • a significantly extended treatment of multiscale modeling of solidification and its applications to commercial alloys • a survey of new topics such as solidification of multicomponent alloys and molecular dynamic modeling • new theories, including a theory on oxide bi-films in the treatment of shrinkage problems • an in-depth treatment of the theoretical aspects of the solidification of the most important commercial alloys including steel, cast iron, aluminum-silicon eutectics, and superalloys • updated tables of material constants.
Length-scale in solidification analysis -- Thermodynamic concepts - Equilibrium and non-equilibrium during solidification -- Nucleation and growth kinetics – Nanoscale solidification -- Fundamentals of transport phenomena as applied to solidification processing -- Diffusive mass transport at the macroscale -- Diffusive energy transport at the macroscale -- Momentum mass transport at the macroscale -- Diffusive mass transport at the microscale - micro-solute redistribution and microsegregation -- Solidification of single-phase alloys – cells and dendrites -- Solidification of two-phase alloys – Micro-scale solidification -- Solidification of multi-component alloys -- Microshrinkage -- Rapid solidification and amorphous alloys -- Semi-solid processing -- Solidification of Metal Matrix Composites -- Multiscale modeling of solidification -- Numerical macro-scale modeling of solidification -- Numerical micro-scale modeling of solidification -- Solidification of some casting alloys of commercial significance.
Keywords: Metals; Crystallography; Mechanics; Mechanics, Applied; Metallic Materials; Crystallography and Scattering Methods; Solid Mechanics